Territorial Issues of Agricultural Sector Development in Andijan Province - Izzatjon Ibrahimjon oglu Abbosov; Husniddin Urozdavlat oglu Kholikov (Zien Journals, 2021)
This article covers regional issues of agricultural development in Andijan region. The regional land fund and agricultural production indicators were analyzed
Keywords: agriculture; land fund; irrigated lands; cotton; vegetables; cereals; development